Antenna incorporated with Electromagnetic Bandgap (EBG) for wearable application at 2.4 GHz wireless bands - Ashyap, A. Y.I . (Institute of Electrical and Electronics Engineers Inc., 2016)
In this work, textile antenna incorporated with an Electromagnetic Bandgap (EBG) structure known as high impedance surface for wearable applications at 2.4 GHz wireless band is designed and presented. The antenna and EBG structures (EBGs) are made from common denim fabrics substrate material with dielectric constant of 2.3405 while the radiating elements are made from copper tape. The performances of the antenna incorporated with EBG under bending conditions are presented. The simulated results of the EBG is verified through measurement which shows a good agreement between the simulated and measured results also been documented. The overall results indicate that the possibility to integrate single band antenna with EBG structure using fabric denim material for wearable applications.